Cell-mediated immunity in operable bronchial carcinoma: the effect of injecting irradiated autologous tumour cells and BCG. Issue 1 (February 1979) - Stack, B H; McSwan, N; Stirling, J M; Hole, D J; Parratt, D; Spilg, W G; Gillis, C R; McHattie, I; Green, A G; White, R G; Turner, M A
Abstract : In 52 patients undergoing tests of cell-mediated immunity before surgical resection of bronchial carcinoma a positive tuberculin test result was found in 71% compared with 68% of age- and sex-matched controls. Sensitisation to DNCB occurred in 52% of 37 patients but in 78% of controls. There was depression of lymphocyte transformation by PPD in 19 patients compared with controls (P=0.001), but there was no difference in lymphocyte transformation by PHA or pokeweed mitogen between 34 patients and controls. In a pilot study patients were randomly allocated to autograft (eight) or non-autograft (seven) groups. The autograft group were given an intradermal injection of a suspension of irradiated autologous tumour-cells mixed with intradermal BCG on the day of operation. Tests of cell-mediated immunity were repeated two weeks after operation. Five patients in each group received a course of radiotherapy to the mediastinum three weeks after operation. There was a rise in cutaneous tuberculin reactivity (P=0.08) and total leucocyte count (P=0.09) in the autograft group postoperatively with a fall in total lymphocyte and T lymphocyte counts in the non-autograft group (P less 0.05). These differences, however, were not followed by any difference in the frequency of tumour recurrence or the survival rate two years after operation. The results show that the immunological surveillance mechanism is impaired even in patients with early bronchial carcinoma and that it is possible to overcome postoperative immunological depression with specific immunotherapy combined with BCG. This treatment did not produce any clinical advantage in this small number of patients and the skin lesions caused the patients considerable discomfort.